2008
DOI: 10.1111/j.1471-0528.2008.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of using mesh or grafts in surgery for anterior and/or posterior vaginal wall prolapse: systematic review and meta‐analysis

Abstract: Background The efficacy and safety of mesh/graft in surgery for anterior or posterior pelvic organ prolapse is uncertain.Objectives To systematically review the efficacy and safety of mesh/graft for anterior or posterior vaginal wall prolapse surgery.Search strategy Electronic databases and conference proceedings were searched, experts and manufacturers contacted, and reference lists of retrieved papers scanned.Selection criteria Randomised controlled trials (RCTs), nonrandomised comparative studies, registrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
21

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(115 citation statements)
references
References 51 publications
5
88
1
21
Order By: Relevance
“…Additionally, questionnaires were filled in 1 year postoperatively which may affect the reliability of reporting preoperative symptoms. However, the prevalence of persistent subjective symptoms was comparable to a recent review where urinary symptoms were persistently reported by 22.7% patients and bowel symptoms by 4.3% after surgery using a nonabsorbable mesh [22]. Presumably because of persistent or de novo subjective complaints, satisfaction with the operation was reported by 71% of the respondents.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, questionnaires were filled in 1 year postoperatively which may affect the reliability of reporting preoperative symptoms. However, the prevalence of persistent subjective symptoms was comparable to a recent review where urinary symptoms were persistently reported by 22.7% patients and bowel symptoms by 4.3% after surgery using a nonabsorbable mesh [22]. Presumably because of persistent or de novo subjective complaints, satisfaction with the operation was reported by 71% of the respondents.…”
Section: Discussionsupporting
confidence: 57%
“…Ancak aynı zaman periyodunda subjektif/semptomatik rekürrensde fark yoktur (9,23). Son yıllarda Klinik Mükemmellik Enstitüsü Klavuzu'nda kısa dönemde absorbe olmayan meşin kısa dönemde standart cerrahiye göre daha iyi anatomik sonuçları olsa da uzun dönem fayda ve güvenliği ile ilgili iyi kanıt olmadığının bildirilmesi ve FDA tarafından meş ilişkili komplikasyonların nadir olmadığının ve ciddi komplikasyonlara yol açabileceğinin açıklanmasından sonra anterior vajinal duvar prolapsus cerrahisinde meş kullanımı azalma eğilimindedir (11,24). Dünyada doğal dokular ile onarım yönünde eğilim oluşmaya başlamıştır.…”
Section: Bulgularunclassified
“…Finally, a meta-analysis encompassing 49 studies and more than 4,500 women determined that nonabsorbable synthetic mesh had a significantly lower objective anterior compartment recurrence rate (8.8%) than either absorbable synthetic mesh (23.1%) or biological graft (17.9%). [32] RCTs comparing outcomes after a mesh kit repair and standard anterior colporrhaphy continue to emerge. Nguyen and Burchette [33] cited a significantly higher anatomic success rate (89%) 12 months after Perigee (AMS Inc., Minnetonka, MN) compared with 55% after anterior colporrhaphy.…”
Section: Interposition Grafts For Pop Repairmentioning
confidence: 99%